2019
DOI: 10.1017/s0033291719000485
|View full text |Cite
|
Sign up to set email alerts
|

Childhood and adolescent psychotic experiences and risk of mental disorder: a systematic review and meta-analysis

Abstract: BackgroundPsychotic experiences (PEs) are common in childhood and adolescence and their association with mental disorders is well-established. We aim to conduct a quantitative synthesis the literature on the relationship between childhood and adolescent PEs and (i) any mental disorder; and (ii) specific categories of mental disorder, while stratifying by study design.MethodThree electronic databases (PUBMED, PsycINFO and EMBASE) were searched from inception to August 2017 for all the published literature on ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

13
115
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 194 publications
(139 citation statements)
references
References 37 publications
13
115
2
Order By: Relevance
“…However, children with psychotic symptoms were more likely to experience a higher number of mental health problems in young adulthood compared to children without such symptoms including a broad spectrum of nonpsychotic psychopathology. This is in keeping with previous studies, 7 , 11 , 55 and supports the hypothesis that early psychotic phenomena are part of a latent continuum of common mental distress. 56 In addition, childhood psychotic symptoms were also associated with a wide array of poor functional outcomes, leading to high personal and societal burden.…”
Section: Discussionsupporting
confidence: 92%
“…However, children with psychotic symptoms were more likely to experience a higher number of mental health problems in young adulthood compared to children without such symptoms including a broad spectrum of nonpsychotic psychopathology. This is in keeping with previous studies, 7 , 11 , 55 and supports the hypothesis that early psychotic phenomena are part of a latent continuum of common mental distress. 56 In addition, childhood psychotic symptoms were also associated with a wide array of poor functional outcomes, leading to high personal and societal burden.…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, the current replication study found associations similar to other large cross-sectional studies of PLEs in childhood and adolescence. 20 , 22–26 The current findings underscore that robust and reliable associations between PLEs and the aforementioned factors can be found in middle childhood manifestations of non-clinical psychosis spectrum symptoms.…”
Section: Discussionsupporting
confidence: 62%
“… 14 Notably, research indicates that self-reported PLEs, even those not confirmed with clinical interview, are still clinically relevant and associated with higher rates of psychopathology 15–17 and reduced functioning. 17 , 18 Several large cross-sectional datasets over the past 2 decades have examined the correlates of PLEs, finding associations with racial/ethnic minority status, 19 internalizing symptoms, 20–22 externalizing symptoms, 20 developmental impairments, 23 and cognitive impairments, 23 , 24 including reading, 25 working memory, 26 , 27 and processing speed 28 impairments.…”
Section: Introductionmentioning
confidence: 99%
“…Studies modelling the co-occurrence of common mental disorders (CMD), such as anxiety and depression, and psychotic experiences have revealed that such experiences measure severity of a unitary, latent continuum of common mental distress 1 and correlate with increased comorbidity, suicidality and poorer treatment outcomes. [2][3][4][5][6][7][8] Psychotic experiences also predict propensity to seek treatment from mental health services for persistent mental ill health. 9 However, stringent referral thresholds prevent these individuals accessing secondary mental healthcare services and they are therefore managed in primary mental healthcare settings.…”
mentioning
confidence: 99%